The Relevance of Surah Al-Jinn in Correcting Modern Society’s Understanding of Jinn Myths - Sugihardi Sugihardi; Sugeng Wanto; Nur Aisyah Simamora (Civiliza Publishing, 2026)
This study discusses The Relevance of Surah Al-Jinn in correcting social myths about jinn in modern society. Discussions about jinn in contemporary society are often no longer framed within proper theological understanding, but are instead mixed with myths, superstition, popular culture, and exploitation through digital media. Jinn are frequently perceived as beings possessing absolute power, having knowledge of the unseen, determining human destiny, and serving as the primary cause of various psychological disturbances and mystical phenomena. Such conditions give rise to irrational fear, practices of shamanism, the pursuit of wealth through supernatural means, and society’s dependence on unseen powers outside the boundaries of Islamic teachings. The research method used is library research employing a descriptive analytical approach. Primary data consist of the verses of Surah Al-Jinn and classical as well as contemporary Qur’anic exegesis (tafsir) literature, while secondary data are obtained from books, journals, scientific articles, and other literature related to jinn and social myths in modern society. The findings of this study show that Surah Al-Jinn affirms that jinn are creations of Allah SWT who possess intellect, free will, and moral responsibility similar to human beings. Jinn are not beings with absolute power nor do they possess complete knowledge of the unseen. This study also finds that social myths about jinn in modern society emerge from a combination of incomplete religious understanding, local culture, mystical traditions, and the influence of mass media and social media. Surah Al-Jinn plays an important role in correcting these myths through strengthening the values of monotheism (tawhid), rejecting practices of shamanism and dependence on jinn, and emphasizing that all power and knowledge of the unseen belong solely to Allah SWT. Furthermore, Surah Al-Jinn is also relevant in developing a more rational, moderate, critical, and Qur’an-based mindset in modern society when understanding unseen matters.